2017
DOI: 10.1007/8904_2017_16
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphenylalaninemia Correlated with Global Decrease of Antioxidant Genes Expression in White Blood Cells of Adult Patients with Phenylketonuria

Abstract: Background: Several studies have highlighted disturbance of redox homeostasis in patients with phenylketonuria (PKU) which may be associated with neurological disorders observed in patients, especially during adulthood when phenylalanine restrictive diets are not maintained. The aim of this study was to assess the antioxidant profile in a cohort of PKU patients in comparison to the controls and to evaluate its relation to biochemical parameters especially phenylalaninemia. Methods:We measured RNA expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
(74 reference statements)
0
9
0
1
Order By: Relevance
“…The included studies were published from 1994 [38] to 2023 [39], and their characteristics are detailed in Table 1. Four studies were conducted in Greece [25,27,40,41], three in Turkey [31,42,43], three in Spain [32,44,45], two in Austria [26,46], two in Chile [39,47], two in Japan [29,30], two in the United Kingdom [48,49], two in the USA [38,50], and one each in Germany [51], France [52], Poland [28], and Switzerland [53]. All studies, except for one case-control study [26], were cross-sectional and compared individuals with PKU to healthy controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The included studies were published from 1994 [38] to 2023 [39], and their characteristics are detailed in Table 1. Four studies were conducted in Greece [25,27,40,41], three in Turkey [31,42,43], three in Spain [32,44,45], two in Austria [26,46], two in Chile [39,47], two in Japan [29,30], two in the United Kingdom [48,49], two in the USA [38,50], and one each in Germany [51], France [52], Poland [28], and Switzerland [53]. All studies, except for one case-control study [26], were cross-sectional and compared individuals with PKU to healthy controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…100 **evidence for this came from a single cross-sectional study 98 and, therefore, observed deficits in cognitive performance may be due to individual differences and do not necessarily reflect the trajectory of cognitive ageing in PKU. 82 increased ROS production 51,83,84 inhibition of antioxidant enzymes 51,85 reduced gray matter volume [86][87][88][89] • Decreased Tyr and Trp r and other LNAA 1 decreased dopamine and norepinephrine (Tyr) and serotonin (Trp) 1 disruptions in protein synthesis 90…”
Section: Gastrointestinal Pathologymentioning
confidence: 99%
“…El glutatión tiene funciones de detoxificación y sirve como almacenamiento y transporte de cisteína, es esencial para la proliferación celular y tiene un papel importante en la apoptosis, ya que la disminución de la cantidad de glutatión es permisiva para la activación de caspasas y la progresión de los mecanismos de apoptosis, en el cerebro se comporta como neurohormona y se ha observado que la deficiencia del mismo está asociada a menor sobrevida de neuronas dopaminérgicas (31). En cuanto a otras defensas antioxidantes no enzimáticas, se ha observado disminución en los niveles de selenio, alfa tocoferol y ácido úrico (32,33). Otra causa de daño significativo en los tejidos es la disminución de ubiquinona-10 debido a que la fenilalanina puede inhibir la acción de la enzima 3-hidroxi-3-metilglutaril-CoA reductasa encargada no solo de la síntesis de colesterol sino también de ubiquinona-10 antioxidante lipofílico que previene la peroxidación de lípidos y desempeña un papel clave en la protección de las membranas biológicas, además ayuda a reciclar un antioxidante natural: la vitamina E (34)(35)(36).…”
Section: Estrés Oxidativounclassified